Beyond the Coffee Cup: The Functions of Cafés in Bishkek. Issue 3 (16th March 2023) - Simkin, Paulina; Schmidt, Matthias
Abstract: Over just a few years, numerous Western-style cafés have opened in Kyrgyzstan's capital and gained popularity. In contrast to existing food-service venues, these new cafés provide superior service, creating incentives to linger. Based on Oldenburg's theory of the 'third place', this article analyses the functions of these cafés and discusses their significance for Bishkek society. Three main functions are identified: first, providing an alternative space for activities usually carried out at home or in the workplace; second, creating a sense of global affiliation; and third, providing a space for solitude within an otherwise traditionally communitarian and family-based society, thus enabling a process of individualisation.